Non‐invasive fibrosis markers for assessment of liver fibrosis in chronic hepatitis delta. Issue 5 (4th February 2023) - Kalkan, Çağdaş; Yılmaz, Yusufcan; Erdoğan, Beyza Doğanay; Savaş, Berna; Yurdcu, Esra; Çalışkan, Aysun; Keskin, Onur; Gencdal, Genco; Zeybel, Müjdat; Törüner, Murat; Bozdayi, A. Mithat; Idilman, Ramazan; et al.
Abstract: Assessment of liver fibrosis by non‐invasive means is clinically important. Studies in chronic hepatitis delta (CHD) are scarce. We evaluated the performance of eight serum fibrosis markers [fibrosis‐4 score (FIB‐4), aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AAR), age‐platelet index (API), AST‐to platelet‐ratio‐index (APRI), Goteborg University Cirrhosis Index (GUCI), Lok index, cirrhosis discriminant score (CDS) and Hui score] in CHD and chronic hepatitis B (CHB). Liver stiffness was assessed by transient elastography (TE) in CHD. The ability of fibrosis markers to detect significant fibrosis and cirrhosis were evaluated in 202 CHB and 108 CHD patients using published and new cut‐offs through receiver operating characteristics (ROC) analysis. The latter was also applied to obtain cut‐offs for TE. APRI, Fib‐4, API and Hui score were assessed for significant fibrosis, and APRI, GUCI, Lok index, CDS and AAR for cirrhosis determination. Fibrosis markers displayed weak performance in CHB for significant fibrosis with area under ROC (AUROC) curves between 0.62 and 0.71. They did slightly better for CHD. TE displayed an AUROC of 0.92 and performed better than serum fibrosis markers ( p < 0.05 for fibrosis markers). For cirrhosis determination, CDS and Lok Index displayed an AUROC of 088 and 0.89 in CHB and GUCI, Lok index and APRI displayed AUROCs around 0.90 in CHD. TE displayed the best AUROC (0.95). Hence TE is superior to serum fibrosis markers for diagnosing significant liver fibrosis and cirrhosis. GUCI, Lok index and APRI displayed a reasonable performance in CHD, which needs further confirmation.